Table of Content - -, (Journal of Economic, Administrative and Legal Sciences, 2024)
Table of Content1. The validity of evidence derived from invalid procedures (A foundational study)Dr. Badr Fahd Hndi Aljohani2. Arbitration Agreement Provisions in Oil Franchise Contracts Disputes - Comparative Study – Upon Application to GCC CountriesDr. Fadwa Mohammed Ali Badwi3. Judicial Immunity of Diplomatic MissionsMrs. Abrar Jamal Alamoudi4. Activating the developmental social role of the Social Solidarity Fund at King Saud University )Proposed template(Mrs. Deem Saleem Alotiby5. The inflation function in the Sudanese economy for the period (1992-2022)Ebtihag Hashim Mohammed Algzoli6. The Reality of Using Digital Platforms and their Impact on Achieving Social Solidarity, the (Ehsan) Platform as a ModelProf. Fahad Mohammed Abed7. Internal Marketing and Anti-Productive Work Behaviors (Relationship and Effect): An Applied Study at Taif UniversityProf. Kholoud Ragheb Alqutub
Keywords: Journal of Economic, Administrative and Legal Sciences